The Effect of Compensation and Person-Job Fit on Work Engagement in Media Workers in Cirebon City - Faiqoh Faiqoh; Kamelia Putri (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the effect of compensation and person-job fit on work engagement among media workers residing in Cirebon City. The study employed a quantitative survey method, utilizing multiple linear regression analysis on data collected from 130 respondents. The results show that person-job fit has a significant influence on work engagement (r = 0.560; p < 0.000), while compensation shows a significant relationship with work engagement (r = 0.227; p > 0.005), and person-job fit has a significant influence on work engagement (r = 0.260; p < 0.001). These two independent variables explain 32% of the variation in work engagement (R² = 0.320). The validity and reliability of the regression model have been confirmed through classical assumption testing. These findings emphasise the importance of alignment between individuals and their jobs in enhancing work engagement in the dynamic media industry, which does not solely rely on financial incentives. The implications of this study encourage media organisations to prioritise selection and management of human resources based on person-job fit for the sustainability and productivity of the workforce.